Strategi Pengembangan Usaha dan Pemasaran Benih Ikan Patin Siam (Pangasianodon hypopthalmus) Dengan Sistem Jejaring pada Cabang Dinas Kelautan dan Perikanan Wilayah Utara Provinsi Jawa Barat - Pramono, Titus; Suryahadi, -; Trilaksani, Wini (Institut Pertanian Bogor, 2019)
The production of Siam-catfish (Pangasianodon hypopthalmus) seeds in Subang, West Java can not meet the market demand yet. The production of Siam-catfish seeds need to be improved especially by the main supplier namely the North Branch of Marine and fisheries service of West Java province (CDKPWU) with a partnership pattern between core and plasma. The purposes of this study were to identify internal and external factors that influence the marketing of Siam-catfish seeds with a network system between CDKPWU and partners, to identify advantages and disadvantages in the network process that occurs between CDKPWU and the partners, and trying to develop the most effective business and marketing srategy of Siam-catfish seeds in order to reach maximum output and outcome. The methods used in this study were as follows: (1) Valuable, Rare, Imitate to Cost and Organized Analysis (VRIO), (2) Political-Legal, Economic, Social, Technology Analysis (PEST), (3) Internal Factor Evaluation Matrix (IFE), (4) External Factor Evaluation Matrix (EFE), (5) Internal External (IE) Matrix, (6) Analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) and (7) Quantitative Strategic Planning Matrix (QSPM) Analysis. The result of IFE and EFE matrix indicated that the company's position was stable in response to external situation. The total score of IFE matrix was 3.38, indicating that the strength of CDKPWU can overcome weaknesses very well. The total score of EFE matrix was 2.59, describing that CDKPWU was good enough in responding to opportunities and minimizing threats. The results of the SWOT analysis show nine alternative strategy formulations in which three alternative formulation priorities were (1) Expanding the production partnership network to increase production and increase community income, (2) Maintaining good seed quality and production process technology, (3) Utilizing partnerships to establish good relationship and communication with relevant agencies. Based on the QSPM matrix analysis, the priority strategies are obtained to be implemented, namely expanding the production partnership network to increase production and increase community income